Factors and causes of the destruction of urbanization in the Middle Maghreb - Tahri, Hakim Kaddour; belghazi, messaoud (The Algerian Historical Journal, 2026)
This research revolves around the factors and causes of the destruction of Islamic urbanism. Many of the reasons led to the destruction of many Islamic cities, especially in the middle Maghreb. Historical and geographical sources have been detailed in this section. Expansive political for those independent states, and limiting the search to four basic elements so that detailed elements overlap in it. The natural, human, and economic factor and the impact of epidemics are elements that destroy urbanization, both directly and indirectly. These are the causes and the summary: This research revolves around the factors and causes of the destruction of Islamic urbanism. Many of the reasons led to the destruction of many Islamic cities, especially in the central Maghreb. Historical and geographical sources have been detailed in this section. Expansive political for those independent states, and limiting the search to four basic elements so that detailed elements overlap in it. The natural, human, and economic factor and the impact of epidemics are elements that destroy urbanization, both directly and indirectly. These are the causes and the destructive for Imran. destructive for Imran. the contents of the article). Enter your abstract here (an abstract is a brief, comprehensive summary of the contents of the article).